2022
DOI: 10.1103/physrevlett.129.125301
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin Spectroscopy of Metastable Superfluid Helium-4

Abstract: We report measurements of the Brillouin frequencies of acoustically driven metastable states of superfluid 4 He at T ∼ 1 K. This is done using a stimulated Brillouin gain spectrometer operating on a confined spatio-temporal domain (∼ 40 µm, 200 ns). Our work questions previous experimental results regarding the metastable states of liquid 4 He and suggests that thermal effects or vortices can play a significant role in the cavitation process. Thanks to our time-resolved measurements, we also find that it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We found that available theoretical 0 K EOS of liquid 4 He at negative pressure correctly reproduce experimental data for the pressure range 0 > P > −1 bar. This set up will be used to measure the EOS of deep metastable states of liquid 4 He at ∼ 1 K in the close vicinity of the destabilization (cavitation) threshold where deviations between the actual EOS and the theoretical one are suspected [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that available theoretical 0 K EOS of liquid 4 He at negative pressure correctly reproduce experimental data for the pressure range 0 > P > −1 bar. This set up will be used to measure the EOS of deep metastable states of liquid 4 He at ∼ 1 K in the close vicinity of the destabilization (cavitation) threshold where deviations between the actual EOS and the theoretical one are suspected [19].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the interaction volume, they are crossed at an angle θ ∼ 90 • and then superimposed on the acoustic focus, see Fig. 2a) [19]. Brillouin frequencies are measured on a space scale of (2w) 3 = 40 3 µm 3 .…”
Section: Brillouin Frequency Measurementmentioning
confidence: 99%
See 1 more Smart Citation